Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/ane.13550
|View full text |Cite
|
Sign up to set email alerts
|

Neurological side effects of SARS‐CoV‐2 vaccinations

Abstract: Though SARS-CoV-2 vaccinations are usually sold as well tolerated, they can cause mild-to-severe side effects in some patients. 1 Since the benefit for the global population outweighs these adverse reactions, and since political and pecuniary interests create the image of a "safe and indispensable" tool against the currently dominant global burden, there is only moderate reporting and discussion about them. 2There is also an anti-vaccine movement in the world nowadays that also contributes to the biased assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
146
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 135 publications
(152 citation statements)
references
References 34 publications
(50 reference statements)
2
146
0
4
Order By: Relevance
“…SARS-CoV-2 and adverse reactions to SARS-CoV-2 vaccines exhibit a tropism for neuronal structures and tissues [ 9 ]. Molecular mimicry has been proposed as a pathogenic mechanism for COVID-19 vaccine-related neurological side effects [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SARS-CoV-2 and adverse reactions to SARS-CoV-2 vaccines exhibit a tropism for neuronal structures and tissues [ 9 ]. Molecular mimicry has been proposed as a pathogenic mechanism for COVID-19 vaccine-related neurological side effects [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was following the administration of 51,755,447 dosages of the COVID-19 vaccines [ 4 ]. Finsterer [ 9 ] in his review paper published in November 2021, reported 11 published cases of transverse myelitis following COVID-19 vaccines, listing this complication as the fourth most common neurological serious adverse effect. Seven cases occurred following the ChAdOx1 nCoV-19 vaccine while one published case occurred after an mRNA vaccine (Moderna) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since SARS-CoV-2 vaccinations of any brand are not free of side effects [ 6 ], it would be interesting to know if the index patient reported any complaints in addition to fever and dyspnoea. Since headache is the most frequent neurological side effect and since headache can trigger TTS, we would like to know if the patient complained of a headache.…”
mentioning
confidence: 99%
“…Since the third most frequent neurological side effect of SARS-CoV-2 vaccinations is venous sinus thrombosis (VST), and VST is compulsorily associated with headache, we would like to know if there were any indications for VST. Since Guillain Barre syndrome (GBS) is the second most frequent neurological side effect of SARS-CoV-2 vaccinations [ 6 ], and GBS can go along with dysautonomia either in association with motor or sensory deficits or without, we would like to know if pure dysautonomic GBS was appropriately excluded. The authors themselves consider a sympatho-vagal imbalance towards adrenergic predominance as a possible pathophysiological mechanism.…”
mentioning
confidence: 99%